Pulmonary fibrosis in patients with COVID-19: A retrospective study - Li, Fanglin; Deng, Jiayi; Song, Yongqiang; Wu, Chenfang; Yu, Bo; Wang, Guyi; Li, Jinxiu; Zhong, Yanjun; Liang, Fang (Frontiers in Cellular and Infection Microbiology, 2022)
1.1 Background: Coronavirus disease 2019 (COVID-19) pandemic has caused substantial threats to people’s physical health and lives, claiming the lives of over 6 million people worldwide. Although the mortality rate of COVID-19 is very low, many survivors may have different degrees and various sequelae. Previous studies have shown that pulmonary fibrosis (PF) were common on discharged COVID-19 patients, and PF itself is a poor prognostic factor. 1.2 Methods: 227 COVID-19 hospitalized patients' clinical and laboratory data from the first 15 days following admission were collected in this retrospective study. Groups were based on with or without PF of COVID-19. Categorical variables were compared with the chi-square test or Fisher’s exact test. Continuous variables were tested by Wilcoxon rank-sum test for the non-normal distribution. Spearman correlations were used to assess the correlations between PF with clinic parameters of multiple time points. Univariate and multivariate logistic regression were used to analyze for risk factors of COVID-19 patients with pulmonary fibrosis. 1.3 Results: Sixty cases of COVID-19 patients were diagnosed with PF. Compared with 167 non-PF patients, those with PF were older and had higher proportions of fever, shortness of breath, hemoptysis, abdominal pain, hypertension, cardiovascular, diabetes, high flow nasal cannula (HFNC), severe disease, and virus shedding duration. Furthermore, the correlation analysis between PF and clinic parameters showed that PF were positively related to the C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), and negatively correlated with hemoglobin (HGB) and albumin (ALB) at all time points in the first 15 days after admission. Moreover, We found that PF were significantly correlated with coagulation indexes prothrombin time (PT), activated partial thromboplastin time (APTT), fibrinogen (Fib) and fibrinolysis index D-Dimer at some phases. In addition, Univariate logistic regression analyses showed that age, fever, shortness of breath, hemoptysis, hypertension, cardiovascular, diabetes, HFNC, severe disease were the risk factors of COVID-19 patients with PF. However, multivariate logistic regression showed that age was the risk factor of COVID-19 patients with PF. 1.4 Conclusion: Combining various factors, advanced age is an independent risk factor of COVID-19 patients with PF. PF was significantly related with clinic parameter of inflammation/coagulopathy/fibrinolysis.